Yeast-Based Biosynthesis of Natural Products From Xylose - Zha, Jian; Yuwen, Miaomiao; Qian, Weidong; Wu, Xia (Frontiers in Bioengineering and Biotechnology, 2021)
Xylose is the second most abundant sugar in lignocellulosic hydrolysates. Transformation of xylose into valuable chemicals, such as plant natural products, is a feasible and sustainable route to industrializing biorefinery of biomass materials. Yeast strains, including Saccharomyces cerevisiae, Scheffersomyces stipitis, and Yarrowia lipolytica, display some paramount advantages in expressing heterologous enzymes and pathways from various sources, and have been engineered extensively to produce natural products. In this review, we summarize the advances in the development of metabolically engineered yeasts to produce natural products from xylose, including aromatics, terpenoids, and flavonoids. The state-of-the-art metabolic engineering strategies and representative examples are reviewed. Future challenges and perspectives are also discussed on yeast engineering for commercial production of natural products using xylose as feedstocks.